Out of Place in Outer Space?: Exploring Orbital Debris through Geographical Imaginations. Issue 1 (1st September 2021) - Hunter, Hannah; Nelson, Elizabeth
Abstract: Increasing human activity in orbital space has resulted in copious material externalities known as "orbital debris." These objects threaten the orbital operations of hegemonic stakeholders including states, corporations, and scientists, for whom debris present a significant problem. We argue that the geographical imaginations of powerful stakeholders shape conceptions of orbital debris and limit engagement with these objects. By engaging with interdisciplinary literature that considers orbital debris and geographical imaginations of outer space, we encourage a more capacious approach to orbital debris that goes beyond hegemonic narratives focused on functionality. We explore the connections between debris and injustice, arguing that these objects must also be considered in relation to terrestrial power and ecology. We then contemplate the possibilities that counter-hegemonic framings present when considering speculative futures of orbital space. In these ways, we explore how and why debris are variously engaged with as pollutants, risks, opportunities, or otherwise.